2018
DOI: 10.1002/gj.3181
|View full text |Cite
|
Sign up to set email alerts
|

Some evolutionary patterns of palaeokarst developed in Pleistocene deposits (Ebro Basin, NE Spain): Improving geohazard awareness in present‐day karst

Abstract: Pleistocene detrital deposits in the central Ebro Basin frequently show deformation features due mainly to karstification in the underlying Neogene evaporites. In 123 cases, estimation of parameters of shape and minimum volume of materials involved was accomplished. Six of them were analysed in more detail to establish the main processes involved in their genesis and the succession of events. All the deformation features in the selected sites are synsedimentary. To achieve the objectives, intense fieldwork was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Buried, collapsed paleokarst systems can form carbonate petroleum reservoirs including those explored in the Fort Worth Basin (FWB) (e.g., Dou et al, 2011; Kerans, 1988; Loucks & Anderson, 1985), the Lower Cretaceous Golden Lane field in eastern Mexico (Coogan et al, 1972; Viniegra & Castillo‐Tejero, 1970), the Tarim Basin in China (e.g., Desheng et al, 1996; Maoshan et al, 2011; Qi et al, 2014; Zeng et al, 2011), and other paleokarst‐related fields reported in previous works (e.g., Andre & Doulcet, 1970; Loucks, 1999; Mazzullo & Mazzullo, 1970; Zhai & Zha, 1982). In addition, collapsed paleokarst systems pose potential drilling hazards due to the weakness of the paleokarst zones (Qi et al, 2014; Soriano et al, 2019; Zhao et al, 2018). Therefore, delineating subsurface collapsed paleokarst systems is important for petroleum reservoir characterization and production.…”
Section: Introductionmentioning
confidence: 99%
“…Buried, collapsed paleokarst systems can form carbonate petroleum reservoirs including those explored in the Fort Worth Basin (FWB) (e.g., Dou et al, 2011; Kerans, 1988; Loucks & Anderson, 1985), the Lower Cretaceous Golden Lane field in eastern Mexico (Coogan et al, 1972; Viniegra & Castillo‐Tejero, 1970), the Tarim Basin in China (e.g., Desheng et al, 1996; Maoshan et al, 2011; Qi et al, 2014; Zeng et al, 2011), and other paleokarst‐related fields reported in previous works (e.g., Andre & Doulcet, 1970; Loucks, 1999; Mazzullo & Mazzullo, 1970; Zhai & Zha, 1982). In addition, collapsed paleokarst systems pose potential drilling hazards due to the weakness of the paleokarst zones (Qi et al, 2014; Soriano et al, 2019; Zhao et al, 2018). Therefore, delineating subsurface collapsed paleokarst systems is important for petroleum reservoir characterization and production.…”
Section: Introductionmentioning
confidence: 99%
“…The rate and distance of eolian transportation strongly depend on grain ability and availability (grainsize and shape), terrain and wind strength (Evans and Reed, 2007;Varga et al, 2011;Kok et al, 2012;Vandenberghe, 2013;Újvári et al, 2016). Allochthonous karst depression, cave and fissurefill sediments are mostly believed to be originated from local sources (Pickford and Mein, 1988;Atalay, 1997;Evans and Reed, 2007;Peresani et al, 2008;Evans and Soreghan, 2015;Muttoni et al, 2017), and considered to be derived from the terrain directly overlying the fracture networks on carbonates (Bosch and White, 2007;Costantini et al, 2009;Mikulčić Pavlaković et al, 2011;Gil et al, 2013;Al-Farraj et al, 2014;Peng et al, 2019;Soriano et al, 2019). Only a few studies have recognized the link between cave and fissure sediments and windblown dust (Coude-Gaussen et al, 1984;Villa et al, 1995;Evans and Reed, 2007;Merino and Banerjee, 2008;Rellini et al, 2013;Evans and Soreghan, 2015;Andreucci et al, 2017;Kovács et al, 2017;Bosák and Zupan Hajna, 2018;Durn et al, 2018;Ge et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The zoning to quantify the recharge by rainfall was performed at two levels: (1) peripheral sub-basins and ( 2) the salt flat nucleus, mixing zone and alluvial fans. The first correspond to the most elevated areas located between 2,400 and 5,500 m a.s.l.…”
Section: Rainfall Gradient)mentioning
confidence: 99%
“…Nevertheless, 3D regional scale models are needed for the management of any hydrogeological system. In the case of coastal systems, this problem is solved in two ways: (1) 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation